Social Empowerment Melalui Investasi Ternak Sapi Bali di Desa Pattappa Kecamatan Pujananting Kabupaten Barru - Lili Cahyati,; Mustari Mustafa,; Muzdalifah Sahib, (Jurnal Berita Sosial, 2023)
This type of research is included in the descriptive qualitative research using a research approach, namely the sociological approach. Furthermore, the data sources used are primary and secoondary data. For data collection through observation, interviews, and documentation. Then the data management and analysis techniques go through three stages, namely: data reduction, data presentation, and conclusions. The results of this study are that there are two form of social empowerments activities for the community through investing in Bali cattle farm, namely in the institutional and economic fields by socializing and training to the community. The public”s perception of investing in Bali cattle farm is as a process of empowerment, has ecological and social impact, is participatory and a sustainable activity. The implications of this research are 1) There is a need to increase collaboration between the Pattappa Village government and the community for the smooth process of this livestock investment activity. This includes intense discussion for the smooth process of this carried out so that the social empowerment process can run well. 2) through this research, it is hoped that it will become a matter of concern for the local government and the community to continue synergizing in utilization of existing resources in Pattappa Village. In addition, the results of this study can be used as reference for students, especially those related to social empowerment and livestock investment.